The impact of lymphadenectomy on the survival of patients with stage I ovarian clear cell carcinoma - Tingting Li; Tingting Li; Chunyan Tan; Chunyan Tan; Sixia Xie; Sixia Xie; Hongjing Wang; Hongjing Wang (Frontiers in Oncology)
ObjectiveTo assess the impact of lymphadenectomy on the survival of patients with stage I ovarian clear cell carcinoma (OCCC).MethodsThe records of 93 patients with stage I OCCC treated between January 2012 and December 2019 were reviewed retrospectively. The relationships between survival outcomes and the number and region of removed lymph nodes (LNs) were assessed, and the independent prognostic factors were analyzed.ResultsThe median number of LNs resected in 93 patients was 24. These patients were divided into two groups based on the median number; overall survival (OS) and recurrence-free survival (RFS) differed significantly between the two groups. Patients were also grouped by the region of the LNs: the pelvic lymph node dissection (PLND) and PLND and para-aortic. Moreover, no differences in OS or RFS were observed between the two groups. Cox regression analysis demonstrated that the number of removed LNs was a significant and independent prognostic factor for poor RFS.ConclusionThis study exhibited that the number of removed LNs, as an important measure of adequate lymphadenectomy for stage I OCCC, contributed to improved RFS and OS. An independent prognostic factor for stage I OCCC was the number of dissected LNs.